SOCIAL GUIDANCE FOR DRUG CLIENTS WITH A COMMUNITY DEVELOPMENT APPROACH IN MANGGUL VILLAGE - Andini, Ahlamia; Equatora, Muhammad Ali (Universitas Nusa Cendana, 2025)
This study aims to explore the effectiveness of social guidance for drug clients using a community development approach in Manggul Village, Lahat. Given the high rate of drug abuse in the community, this approach is expected to create an environment that supports the process of rehabilitation and social reintegration for clients. This study uses a qualitative method with a case study approach, involving in-depth interviews, participatory observation, and document analysis related to the social guidance program that has been implemented. This study also found that collaboration between the community and community leaders is critical in creating a sustainable program. With strong support from various parties, this program reduces the stigma against drug users and provides better access for clients to get the help they need. In addition, more systematic monitoring and evaluation need to be carried out to ensure the sustainability and effectiveness of the program. Through the development and implementation of the right strategy, it is hoped that this program can have a greater impact in overcoming the problem of drug abuse in Manggul Village and become a model for other areas. The results of the study indicated that the community development approach has succeeded in increasing public awareness of the dangers of narcotics and the importance of support for clients. In addition, social guidance carried out through group therapy and individual counseling has proven effective in helping clients overcome personal and emotional problems related to drug abuse. Keywords: Social Guidance; Narcotics Clients; Community Development; Manggul Village